PENGARUH LATIHAN PUSH-UP DAN KADAR LEMAK TUBUH TERHADAP KETERAMPILAN SMASH DALAM PERMAINAN BULUTANGKIS KABUPATEN TAKALAR - Sudiadharma, Sudiadharma; Rahman, Abdul (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
This experimental study aims to determine the effect of push-up training involving body fat levels on the smash skills of badminton games. Body fat levels consist of high and low. The experimental method uses a